Blood flow restriction training in microgravity: a review of multisystem physiological benefits and implementation challenges for long-duration space missions - Mingzhen Hu; Wei Li; Qiushi Yin; Yuqing Liu; Lin Chen; Qin Ru; Guodong Xu; Yuxiang Wu (npj Microgravity)
Abstract This review evaluates BFRT as a novel countermeasure against multisystem deconditioning (muscle atrophy, bone loss, cardiovascular impairment) during long-duration space missions. BFRT combines low-load exercise with vascular occlusion, mimicking high-intensity benefits while reducing equipment needs. We synthesize evidence for BFRT’s efficacy in microgravity analogs, discusses implementation challenges (equipment adaptation, safety protocols, sex-specific responses), and highlight its potential as a space-efficient adjunct to current exercise regimens, informing future mission planning.